2019
DOI: 10.4055/cios.2019.11.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Computed Tomography-Based Navigation for Cup Placement in Revision Total Hip Arthroplasty

Abstract: Background Navigation systems are an effective tool to improve the installation accuracy of the cup in primary total hip arthroplasty. This study aimed to evaluate the efficacy of a computed tomography-based navigation system in achieving optimal installation accuracy of implants in revision total hip arthroplasty and to clarify the usefulness of the navigation system. Methods We conducted a retrospective study of 23 hips in 23 patients who underwent revision total hip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…They found the center of rotation of the hip and length discrepancy was accurately recovered as preoperative plan without signs of loosening, subsidence, or osteolysis at final follow-up [25]. Compared with CT-based navigation, the 3D preoperative simulation technology and 3D model had lower accuracy [2628]. Additionally, previous study reported there was a high accuracy by using imageless navigation-assisted cup positioning [29].…”
Section: Discussionmentioning
confidence: 99%
“…They found the center of rotation of the hip and length discrepancy was accurately recovered as preoperative plan without signs of loosening, subsidence, or osteolysis at final follow-up [25]. Compared with CT-based navigation, the 3D preoperative simulation technology and 3D model had lower accuracy [2628]. Additionally, previous study reported there was a high accuracy by using imageless navigation-assisted cup positioning [29].…”
Section: Discussionmentioning
confidence: 99%
“…Combined anteversion, which is defined as the sum of the anteversion of the cup and that of the femoral component, is used to further illustrate the ideal orientation for the stability of prostheses. Many studies have summarized the angle of combined anteversion in clinic practice 6,8,15 . However, the range of combined anteversion varies in different reports.…”
Section: Introductionmentioning
confidence: 99%
“…Dorr concluded that the combined anteversion was 37.6 AE 7 (range, 19 -50 ) 6 . Kubota reported that combined anteversion is 41.2 AE 8.9 with navigation and 33.6 AE 20.5 without navigation 15 . Although the ideal combined anteversion still needs to be investigated, numerous studies have used the combined anteversion technique to guide their operations and achieve good results [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 97 ] 2007 Journal of Arthroplasty 1, 2, 4 Kubota Y. et al. [ 98 ] 2019 Clinical Orthopaedics and Related Research 1, 2, 4 Kurosaka K et al. [ 99 ] 2016 Orthopedics 1, 2, 3, 4 Langlotz U. et al.…”
Section: Appendixmentioning
confidence: 99%